Filling Gaps and Verifying Facts: Assumptions and Credibility Assessment in the Australian Refugee Review Tribunal. (7th June 2018) - Dowd, Rebecca; Hunter, Jill; Liddell, Belinda; McAdam, Jane; Nickerson, Angela; Bryant, Richard
Abstract: This study investigates the assumptions made by decision makers in Australia when adjudicating claims for refugee status and/or complementary protection. By analysing 50 randomly selected cases of the Refugee Review Tribunal, it provides a systematic evaluation of the frequency and importance of assumptions made by Australian Tribunal members, partly replicating an earlier United Kingdom study published in this journal. As a multidisciplinary team of lawyers and psychologists, the authors investigate how Tribunal members' assumptions about human behaviour pervade credibility assessments, and how they shape overall decision making in the asylum context. This study examines the extent to which Tribunal members take account of credibility guidelines and the psychological evidence base to give protection applicants the benefit of the doubt when their claims cannot be verified. Since asylum seekers' futures are determined by the outcome of these decisions, it is argued that the Tribunal should provide a greater level of predictability and consistency in the approach taken in the assessment of their cases.